REARING OF JUVENILE DONKEY-EAR ABALONE (Haliotis asinina) IN FLOW-THROUGH TANKS WITH THE ADDITION OF DIFFERENT SUBSTRATES - Setyono, Dwi Eny Djoko (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2015)
This study investigated the effects of the addition of coral rubble and polyvinylchloride (PVC) guttering as substrates on the growth of donkey-ear abalone (Haliotis asinina) reared in a flow-through water system. The tanks were100 cm long x 50 cm wide x 40 cm deep, filled with sea water up to 30 cm high. Hatchery-produced abalone with a mean initial shell length of 30.9 ± 0.1 mm and wet weight of 5.5 ± 0.1 g were stocked at 25 individuals/tankthat corresponded to stocking densities of ca. 50 abalone/m2 of the bottom area of the tank. Juvenile abalonewere provided with an excess red seaweed Gracilaria spp daily over 175 days. The results show that growth and growth rates in shell length and wet body weight were not significantly different between treatments (P>0.05). Survival rates of juveniles reared in the tank with the addition of coral rubble and/or PVC guttering were 100%, but 98% for juveniles in the tank without the addition of substrate. The average daily growth rates of shell length and wet body weight were 0.087+0.037 mm and 0.088+0.044 g for juveniles reared in the tank with the addition of coral rubble; 0.081+0.030 mm and 0.077+0.032 g for juveniles reared in the tank with the addition of PVC guttering; and 0.082+0.032 mm and 0.078+0.039 g for juveniles reared in tank without addition of substrates.